P53 expression in repair/reactive renal tubular cells: A potential pitfall leading to a false‐positive diagnosis of urine cytology. (16th November 2021) - Enomoto, Kaori; Matsunaga, Toru; Sofue, Tadashi; Nakamura, Akihiro; Hirakawa, Eiichiro; Ibuki, Emi; Haba, Reiji; Kamoshida, Shingo; Ohsaki, Hiroyuki
Abstract: Background: p53 immunostaining is routinely used as a surrogate marker for TP53 mutational status. In urine cytology, p53 immunocytochemistry is reportedly useful in detecting urothelial carcinoma cells as well as in improving the detection sensitivity and specificity. However, to the best of our knowledge, p53 expression in repair/reactive renal tubular cells (RRTCs) from urine cytologic specimens has not been assessed to date. Methods: We evaluated the immunoexpression of p53 and homogentisate 1, 2‐dioxygenase (HGD) antibody, a renal tubular cells marker, in RRTCs using voided urine and renal biopsy samples from 80 patients who were histologically diagnosed with glomerular disease. Results: Repair/reactive renal tubular cells were detected in 68 (68/80, 85%) samples at a mean count of 141.1 cells per sample (range, 5–4220). Immunocytochemical analysis found p53‐positive RRTCs in all the samples (68/68, 100%) with an average p53 positivity rate of RRTCs per sample at 47.7% (range, 3.8%–96.5%). Of the 68 p53‐positive RRTC samples, 38 (55.9%) included cells that were HGD positive for cytoplasm. Similarly, renal biopsy analysis revealed p53‐positive RRTCs in all the specimens (68/68, 100%). All 68 (100%) cases showed RRTCs that were positive for both p53 and HGD. Conclusion: To avoid false positives of p53 immunocytochemistry, cytologists must consider the fact that RRTCs from patients with glomerular disease are positive for p53. Abstract : Although the existence and cytological features of repair/reactive renal tubular cells in urine are not yet widely well known, these cells cytomorphologically mimic cancer cells. This study found that repair/reactive renal tubular cells are positive for p53 immunocytochemistry, which is crucial information for helping to avoid false positives in urine cytology.